What Drives Milk Output In Indonesian Smallholder Dairy Farms? Insights From Pagerjurang - Indrasto, Haryo Bimo Budi; Hidayah, Nur; Afandi, Muslim (Journal of Rural and Regional Innovation Studies, 2024)
Low dairy cow milk productivity remains a key constraint to improving farmer welfare and food security in many developing countries. This study investigates the factors affecting milk production among dairy farmers in Pagerjurang Village, using data from 80 purposively selected respondents. Variables examined include the number of cows, pen area, milking duration, use of concentrate feed, and use of tofu dregs. To address potential endogeneity in the number of cows, the study applies the Two-Stage Least Squares (2SLS) estimation method, with pen area as an instrumental variable. Additionally, robust standard errors and Quantile Regression are used to test the consistency of results across different production levels. The findings reveal that the number of cows and concentrate feed have a significant and positive effect on milk production, indicating the importance of livestock scale and nutritional quality. Pen area, used as an instrument, also proved to be a strong predictor of herd size. Milking duration and tofu dregs showed no significant effect. The quantile regression results suggest that larger-scale farmers benefit more from increased inputs, reflecting potential scale economies. These results highlight the need for integrated and scalable management practices to enhance dairy productivity sustainably.